Letter to the editors: “Efficacy and safety of robotic surgery versus open surgery for hilar cholangiocarcinoma: a systematic review and meta-analysis”: correspondence - Oweira, Hani; Reißfelder, Christoph; Fattal, Mohamad Wahid; Bigourdan, Jean Marc; Chaouch, Mohamed Ali (International journal of surgery, 2025)
An abstract is unavailable.
Gesehen am 16.09.2025